Pengaruh Kompaksi Terhadap Karakteristik Briket Kulit Buah Kakao dan Kulit Biji Jambu Mete - Harlan, Harlan; Kadir, Abd .; Imran, Al Ichlas (Teknik Mesin Universitas Halu Oleo, 2020)
With the increasing population, the need for fuel also increases so that otheralternative sources are needed. One of the renewable energy that needs attention to be developed is agricultural waste such as rice husks, coconut shells, cashew skins, sago fronds, cocoa shells, and other agricultural or plantation waste. This study aims to determine the characteristics of the cocoa pod briquettes and cashew nut shells. The method used in this research is to use variations in pressure at the time of printing, the pressure used is 50 kg/cm2, 100 kg/cm2 and 150 kg/cm2. The characteristics of the briquettes tested were density, moisture content, ash content, heating value and rate of combustion. The results showed that the highest density was 0.91 kg/cm3 with a pressure of 150 kg/cm2 , the highest water content value was 13.84 % with a pressure of 50 kg/cm2 , the highest ash content was 5.16 % at a pressure of 150 kg/cm2, the value of The highest heat is 6024.33 Cal/g with a pressure of 150 kg/cm2, and the longest burning rate is 44 minutes with a pressure of 150 kg/cm2. So it can be concluded that the higher the compacting pressure during printing, the higher the value of density, ash content, heating value, combustion rate and moisture content value are getting better.Keywords: Briquettes, compaction, cocoa skin, cashew seed skin